Human resource management for MBA and Business Masters - Henderson, Iain (Chartered Institute of Personnel and Development, 2017)
Now aimed at a wider readership of management Masters students, this fully updated 3rd edition of Human Resource Management for MBA and Business Masters features a greater international and contemporary focus, fresh case studies, coverage of the impact of new forms of employment and technology on HR, and updated online supporting resources. With diagrams and models throughout, it covers topics such as CSR, organizational culture and change, performance management and talent management, the criticisms of HRM levelled by the Critical Management School and different HRM challenges as they relate to each chapter. Online supporting resources for tutors include an instructor's manual, videos, multiple-choice questions and additional case studies; additional resources for students include multiple-choice questions and additional case studies.